Downdraft Gasification of Oil Palm Frond: Effects of Temperature and Operation Time - Moni, M. N. Z. (2012)
The last years saw a sharp increment in the interest laid on the renewable and the alternative energy sector, mainly due to the depletion of fossil fuel throughout the world for industrial and commercial use. Malaysia is the second largest producer of palm oil, currently holding up to 4.5 million hectares of palm oil plantation in its land. Currently produced at more than 40 million tons a year, only a small portion of oil palm frond (OPF) is used as domestic animals forage and as raw material in small-scale furniture industry, while the rest is left at the plantation floor to naturally decompose. This study introduces OPF as a solid biomass fuel for gasification to produce synthesis gas that can be utilized for heat and energy generation in a cleaner and more efficient manner than direct combustion. OPF was gasified in the downdraft gasifier at 700 to 1000°C reactor temperature with a controlled air supply of 180 to 200 liter per minute. The effects of reactor temperature and operation time to the quality of syngas produced from OPF downdraft gasification were investigated. At a calorific value at around 18 MJ/kg, OPF was found to produce synthesis gas that sustainably burnt in air with a higher heating value of around 5 MJ/Nm3. OPF was found to be optimally producing syngas with desired energy content at a reactor temperature range of 700-900°C and within the first 45 minutes of gasifier operation.